Fatores de risco para o desenvolvimento de candidemia em pacientes com cultura de vigilância de urina positiva para Candida spp - VASCONCELLOS , Isabela Cristina Marocchio (2022)
Hospital acquired fungal infections are responsible for complications in critically ill hospitalized patients who are more susceptible to the development of candidemia in the presence or absence of candiduria. Colonization by Candida spp. can be considered a risk factor for the development of candidemia, and is associated with high mortality and morbidity among hospitalized patients, as the diagnosis and initiation of treatment often occur late. The aim of the study was to characterize candiduria in patients admitted to a tertiary-level hospital and establish risk factors associated with the development of candidemia. Methods: A laboratory and clinical surveillance study was performed with samples of Candida spp. previously isolated from urine surveillance culture of patients admitted to the Intensive Care Unit of the Hospital Regional de Presidente Prudente, located in the western region of São Paulo state, Brazil, during 2019 to 2020. Results: 281 isolated samples of urine culture were analyzed for Candida, from these samples, 125 patients’ medical records treated in the period from 2019 to 2020 were located. Of the 125 patient records reviewed, information on blood culture requests was obtained from 111 medical records. The incidence of candidemia in patients with positive surveillance culture for Candia spp was 17.7 per 1000 admissions. It was possible to notice that in patients with digestive system diseases, as a cause of hospitalization and with a positive urine surveillance culture for Candida spp species, the chance to develop Candidemia is eight times greater than in other patients. In addition, those with Coronary Artery Disease (CAD) were 26 times more likely to have Candidemia than those without this comorbidity. The prevalence of candidemia in patients with a positive urine culture was 1.77%. In the present study, 80.0% of patients who developed candidemia died. We conclude that the possibility of developing candidemia from candiduria is 4.5%, however, the installation of a candidemia condition, regardless of the source, worsens the patient's prognosis.